Pengaruh Harga, Halal Awareness, dan Celebrity Endorser terhadap Keputusan Pembelian Produk Makanan pada E-Commerce: Studi pada Mahasiswa FEBI 2022-2024 - Muhammad Iqbal; Sri Rahma; Achyat Budianto (YASIN, 2026)
Although the development of e-commerce has changed consumer behavior in purchasing food products online, Muslim consumers’ purchase decisions are influenced not only by economic factors, such as price, but also by religious values through halal awareness and social factors through celebrity endorsers. This study aimed to analyze the influence of price, halal awareness, and celebrity endorsers on purchase decisions for halal food products on e-commerce platforms. This study employed a quantitative approach using a survey method involving 95 students of the Faculty of Islamic Economics and Business at UIN Sulthan Thaha Saifuddin Jambi from the 2022–2024 cohorts. Data were collected through questionnaires and analyzed using validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and coefficient of determination (R²) analyses with the assistance of SPSS. The results showed that, partially, price and halal awareness had a positive and significant effect on purchase decisions, whereas celebrity endorsers had no significant effect. Simultaneously, the three variables had a significant effect on purchase decisions, with an F value of 13.926 (p < 0.05). The coefficient of determination (R²) value of 0.315 indicates that 31.5% of the variation in purchase decisions can be explained by price, halal awareness, and celebrity endorsers. These findings confirm that purchase decisions for halal food products on e-commerce platforms are more strongly influenced by price and halal awareness than by promotion through public figures. This study contributes to strengthening the study of Muslim consumer behavior in the context of digital commerce and provides practical implications for business actors to set competitive prices and ensure clarity of product halal status in order to increase consumer trust and purchase decisions.